Have a question? Just ask it: using an anonymous mobile discussion platform for student engagement and peer interaction to support large group teaching - Elaine Tan; Adrian Small; Paul Lewis (Association for Learning Technology, 2020)
This article analyses the pilot of an anonymous question and answer mobile application with a large cohort of undergraduate students (460) enrolled on an Operations Strategy Management module. The mobile application allowed students to pose anonymous questions to both peers and staff, create replies and vote on questions posted by other users. The aim of the pilot was to evaluate how this application could be used to enhance communication, engagement and student learning both inside and outside of class time to overcome some of the challenges presented by large cohort teaching. An initial evaluation was undertaken exploring both the analytics attached to the platform and a thematic analysis of the posts. The initial findings of the pilot were positive, with the majority of students installing and regularly accessing the application with use increasing over time. The questions posed demonstrated engagement beyond surface-level memorisation of module content, and there were indications that the application could be beneficial in supporting student community awareness and interaction within large cohorts.